Enhancing the Management of Student’s Examination Records using an Interactive Website for Tertiary Institutions in Ghana - Danaa, Abukari Abdul Aziz; Diyawu, Mumin (International Journal of Computer (IJC), 2016)
Most tertiary institutions in Ghana still employ the manual process in students’ academic records management process. Updates to records are poorly implemented which results in severe inconsistencies in students records. Generation of Reports to undertake strategic decisions usually takes a lot of time and often generated with errors. Additionally, end of semester results which is supposed to be confidential is usually posted on notice boards for students to access. Prospective students and the general public who need information regarding any aspect of the institution instead of doing so with ease, would either have to spend so much time to contact the institution and may not even be given the needed information. This research seeks to develop a very secure system which will not only provide relevant up-to-date information relating to all aspects of the institution, but also for processing students examination records and online results checking. The system will also provide an internal commincation system between the system administrator and both lecturers and students.